She Inherits, She Sells: community-based theatre to strengthen women’s land rights and entrepreneurship - Najjar, Dina; Oueslati, Dorsaf; Benrais, Brahim; Nidkazza, Zakaria (Taylor and Francis Group, 2025)
Women in the Middle East and North Africa (MENA) region have the lowest rates of land ownership and workforce participation despite increased educational attainment. Sociocultural norms are often cited as the cause. Using the Theatre of the Oppressed methodology, we conducted action research to address harmful norms around women’s inheritance, mobility, sexual harassment, and control over income. Participants were asked to resolve these issues during performances. The plays were performed between February and April 2024, and phone evaluations were collected between February and June 2024. Our play, She Inherits, She Sells, with the motto ‘anyone can act’, was showcased in two Moroccan regions: Fes-Meknes (four villages) and Souss-Massa (five villages). We analysed transcripts of the nine plays and discussions along with hour-long phone interviews (with 189 women and 53 men) to assess whether the plays led to new learnings, changes in thinking, and if participants felt their voices were heard. Findings reveal young women had the most positive experiences: they expressed their opinions more freely, felt entitled to their inheritance, demanded control over their income, and felt confident about reporting sexual harassment. Young men were proactive in addressing violence against women but less so regarding land rights. Conversely, older women felt that asking for inheritance from their brothers and moving without male protection were taboo, and they were less comfortable expressing their opinions during the plays. We recommend increasing the use of such arts-based awareness-raising interventions, especially with youth, as a promising route for social change.